In-Situ Annealed Ti3C2Tx MXene Based All-Solid-State Flexible Zn-Ion Hybrid Micro Supercapacitor Array with Enhanced Stability - Li, La; Liu, Weijia; Jiang, Kai; Chen, Di; Qu, Fengyu; Shen, Guozhen (Nano-Micro Letters, 2021)
Zn-ion hybrid supercapacitors (SCs) are considered as promising energy storage owing to their high energy density compared to traditional SCs. How to realize the miniaturization, patterning, and flexibility of the Zn-ion SCs without affecting the electrochemical performances has special meanings for expanding their applications in wearable integrated electronics. Ti3C2Tx cathode with outstanding conductivity, unique lamellar structure and good mechanical flexibility has been demonstrated tremendous potential in the design of Zn-ion SCs, but achieving long cycling stability and high rate stability is still big challenges. Here, we proposed a facile laser writing approach to fabricate patterned Ti3C2Tx-based Zn-ion micro-supercapacitors (MSCs), followed by the in-situ anneal treatment of the assembled MSCs to improve the long-term stability, which exhibits 80% of the capacitance retention even after 50,000 charge/discharge cycles and superior rate stability. The influence of the cathode thickness on the electrochemical performance of the MSCs is also studied. When the thickness reaches 0.851 µm the maximum areal capacitance of 72.02 mF cm−2 at scan rate of 10 mV s−1, which is 1.77 times higher than that with a thickness of 0.329 µm (35.6 mF cm−2). Moreover, the fabricated Ti3C2Tx based Zn-ion MSCs have excellent flexibility, a digital timer can be driven by the single device even under bending state, a flexible LED displayer of “TiC” logo also can be easily lighted by the MSC arrays under twisting, crimping, and winding conditions, demonstrating the scalable fabrication and application of the fabricated MSCs in portable electronics. Highlights: 1 Flexible Zn-ion hybrid micro-supercapacitors (MSCs) array was fabricated with Ti3C2Tx as the cathode via laser direct writing method, which present ultrastability up to 50,000 cycles after in-situ annealed treatment. 2 A digital timer driven by the obtained single MSC under bending state, together with a flexible LED displayer of the “TiC” logo lighted by the MSC arrays under twisting, crimping and winding conditions demonstrate the great potential application of the MSCs in integrated wearable electronics.